IMPLEMENTASI MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 169 PEKANBARU - Erlisnawati Erlisnawati; Hendri Marhadi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
The problem in this research was social studies student achievement in fourth grade (IV) SDN 169 Pekanbaru still low with average value 63.88 (with KKM 75). The purpose of this research was to improve the student achievement of the fourth grade (IV) SDN 169 Pekanbaru with the implementation of Problem Based Learning model. This research was classroom action research with two cycles in first semester 2015. Before implementation Problem Based Learning average 63.88, after implementation of Problem Based Learning, UH I was 71.25 that improve 11.54% from before exam with average 61.62. UH II was 80.38 that improve 25.83%. Teacher’s activities with the implementation of Problem Based Learning at first meeting of first cycle was 70% (good category), and second meeting was 80% (good category) that improve 10 point. At second cycle, teacher’s activitiesat first meeting was 90% (very good category) that improve 10 point from second meeting of first cycle. Second meeting of second cycle was 95% (very good category) which improve 5 point. Students activities at first meeting of first cycle was 65% (good category), and second meeting 75% (good category) that improve 10 point. At second cycle, student activities at first meeting was 80% (good category) that improve 5 point from second meeting of first cycle. Second meeting of second cycle was 85% (very good category) which improve 5 point. Implementation of Problem Based Learning model can improvedsocial studies student achievement of fourth grade (IV) SDN 169 Pekanbaru.Keywords: problems based learning, sosial studies student’s achievement